Progress on diagnosis and treatment of drug-resistant tuberculosis in line with World Health Organization recommendations in six priority countries in the Western Pacific Region - Oh, Kyung Hyun; Quelapio, Maria Imelda; Morishita, Fukushi; Rahevar, Kalpeshsinh; Yanagawa, Manami; Islam, Tauhid (Western Pacific Surveillance and Response, 2022)
Background: Diagnosis and treatment of drug-resistant tuberculosis (DR-TB) have radically changed in accordance with recommendations from the World Health Organization (WHO) in the past decade, allowing rapid and simple diagnosis and shorter treatment duration with new and repurposed drugs.Methods: A descriptive analysis of the status and progress of DR-TB diagnosis and treatment in six priority countries in the Western Pacific Region was conducted using information from interviews with countries and the WHO TB database.Results: Over the past decade, the use of Xpert MTB/RIF has increased in the six priority countries, in parallel with implementation of national policies and algorithms to use Xpert MTB/RIF as an initial diagnostic test for TB and detection of rifampicin resistance. This has resulted in increases in the number of people diagnosed with multidrug-resistant or rifampicin-resistant TB (MDR/RR-TB). Shorter treatment regimens with new and repurposed drugs have also been adopted for MDR/RR-TB cases, alongside a decentralized model of care, leading to improved treatment outcomes.Discussion: The Western Pacific Region has achieved considerable progress in the diagnosis and treatment of DR-TB, in line with the evolving WHO recommendations in the past decade. The continued commitment of Member States is needed to address remaining challenges, such as the impact of the coronavirus disease pandemic, suboptimal management and health system issues.
Keywords: tuberculosis, drug-resistant; diagnosis; treatment; tuberculosis, multidrug-resistant; rifampicin; Asia; Pacific Islands